2017
DOI: 10.1017/cts.2018.5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost of recruiting healthy volunteers for clinical research studies using an electronic patient portal: A randomized study

Abstract: IntroductionIt is not clear how to effectively recruit healthy research volunteers.MethodsWe developed an electronic health record (EHR)-based algorithm to identify healthy subjects, who were randomly assigned to receive an invitation to join a research registry via the EHR’s patient portal, letters, or phone calls. A follow-up survey assessed contact preferences.ResultsThe EHR algorithm accurately identified 858 healthy subjects. Recruitment rates were low, but occurred more quickly via the EHR patient portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…We utilized a convenience sample via electronic portal recruitment messaging which had a response rate of 20%. However, this is comparable to response rates in other studies utilizing portal recruitment [ 7 , 8 ]. Furthermore, patients who were experiencing psychiatric morbidity may have been more interested and more likely to participate in our study, as the recruitment letter noted that we were studying psychological distress after COVID-19 hospitalization.…”
supporting
confidence: 83%
“…We utilized a convenience sample via electronic portal recruitment messaging which had a response rate of 20%. However, this is comparable to response rates in other studies utilizing portal recruitment [ 7 , 8 ]. Furthermore, patients who were experiencing psychiatric morbidity may have been more interested and more likely to participate in our study, as the recruitment letter noted that we were studying psychological distress after COVID-19 hospitalization.…”
supporting
confidence: 83%
“…These processes may affect many actors in the clinical care setting including patients, nurses, physicians, clinical coordinators, and investigators. Semi-automated recruiting for trials has reportedly been effective in some early studies [10,14,15]; however, implementation of these programs is highly variable making interpretation of the beneficial features difficult. Studies of effects of these Clinical Trial Recruitment Support Systems (CTRSS) frequently report on improved efficiency achieved by reducing man hours per trial participant or by increasing the number of participants referred.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of effects of these Clinical Trial Recruitment Support Systems (CTRSS) frequently report on improved efficiency achieved by reducing man hours per trial participant or by increasing the number of participants referred. However, few report on physician factors, therefore psychological and behavioral factors are not fully understood [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these studies investigated the use of email to pre-warn participants, and our finding may be attributed to a shift in type of contact preference towards email. Specifically, as Samuels et al [ 34 ] found that when asking subjects how they would like to be contacted for future research studies 58% opted for an email whereas only 16% opted for a phone call.…”
Section: Discussionmentioning
confidence: 99%